Fatal Disseminated Aspergillosis in a Patient with Systemic Lupus Erythematosus - Rochelle Hardie; Tracian James-Goulbourne; Monsoon Rashid; Jeremy Sullivan; Yamen Homsi (Case Reports in Infectious Diseases)
Patients with systemic lupus erythematosus (SLE) are at increased risk for infection including opportunistic infections. Fungal infection in particular can be difficult to diagnose and treat and often can be life-threatening in the immunocompromised patient. We present a case in which a patient with SLE presented to the hospital with shortness of breath and cough. Throughout the hospital course, the patient’s condition continued to decline leading to acute respiratory failure, and eventually, the patient expired. Postmortem autopsy revealed invasive fungal aspergillosis infection involving the heart, lungs, and brain. Earlier diagnosis and treatment with empiric antifungals may improve survival in these patients.